Zinc therapy for different causes of diarrhea - Abdillah, Hafaz Zakky; Supriatmo, Supriatmo; Deliana, Melda; Nafianti, Selvi; Sinuhaji, Atan Baas (Paediatrica Indonesiana, 2013)
Background The incidence of diarrhea in Indonesia has declined in the past five years. In spite of the increasing number of studies on the treatment for acute diarrhea, especially the use of zinc, it is not known if bacterial vs. non-bacterial etiology makes a difference in the reduction of severity of acute diarrhea in children on zinc therapy. Objective To assess the effect of zinc therapy in reducing the severity of acute bacterial and non-bacterial diarrhea. Methods We performed a cross-sectional study in the Secanggang District, Lan gkat Regen cy of North Sumat era, from August to November 2009 in children aged 2 months to 14 years . Microscopic stool examination s were undertaken to separate subjects into the acute bacterial or non-bacterial diarrhea groups. Both groups received 10 mg/day ofzinc sulphate for subjects aged <6 months or 20 mg/day for those aged 2:6 months for 10 days. Measurement of disease severity was based on the frequency of diarrhea (times/day) and the duration of diarrhea (hours) after initial drug consumption . We performed indepen dent T test for statistical an alysis. Results Sixty-two children participated in this study, with 31 children in the acute bacterial group, and the remainder in the non-bacterial group. There were no significant differences between the two gro ups in frequency of diarrhea (2 .61 vs 2.70 times/day, respectively, P=0.27) or in duration of diarrhea (63.39 vs 66.68 hours, respectively, P= 0.06) . Conclusion Zinc is not more effective in reducing the severity of acute bacterial diarrhea compared to non-bacterial diarrhea in children.